حقوق الجوار المعنوية وفوائدها في ضوء السنة النبوية = The moral rights of the neighbours according to the Prophetic Sunnah - Ali, Nuhu; Mansour, Saad eldin (IIUM Press, International Islamic University Malaysia, 2020)
This study seeks to explore and present the status of neighbours and their moral rights from the Islamic perspective. The issue raised by this paper was the neglect of many of the rights of neighbours and the reported conflicts that occurred among neighbours. This paper argues that guidance and teachings concerning the issues of neighbourhood can be traced in the collections of hadith of the Prophet PBUH and that Islam has already given emphasis on the moral rights of neighbours whether they are Muslims or non-Muslim neighbours. The research adopted the deductive and analytical methods to collect hadith, interpret its texts and analyse the intended meanings and aims from the Sunnah. The resultshows that taking care of neighbours secures a high position in Islam since that it is related to his status in the Hereafter. The Prophet, as learned from these hadiths, has shown the best example of caring for neighbours and making the neighbourhood thesafe place for everyone.*Post-doctoral Researcher, Department of Qurʾān and Sunnah Studies, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia (IIUM), Kuala Lumpur, Malaysia. Email: nuhuali96@gmail.com**Associate Professor, Department of Qurʾān and Sunnah Studies, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia (IIUM), Kuala Lumpur, Malaysia. Email: eldin@iium.edu.my